2017
DOI: 10.1111/are.13578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary vitamin C on growth, gonad development and antioxidant ability of on-growing gibel carp (Carassius auratus gibelio var. CAS III)

Abstract: An 88-day experiment was conducted in a flowing system to evaluate the effects of dietary vitamin C on growth, body composition, antioxidant and gonad development of on-growing gibel carp. Triplicate tanks of gibel carp (77.2 AE 0.1 g) were randomly fed with one of seven experimental diets containing L-ascorbic acid of 0, 101.1, 188.5, 313.1, 444.1, 582.1 and 747.0 mg/kg, respectively. The results showed that specific growth rate (SGR) and feed efficiency (FE) of fish were not affected by dietary L-ascorbic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
5
6
0
Order By: Relevance
“…In the present study, the hepatic SOD, T‐AOC and CAT activities increased with vitamin C levels from 2.24 to 171.16 mg/kg, beyond which they decreased. These data suggested that, dietary vitamin C enhanced the hepatic SOD, T‐AOC and CAT activities (Cheng, Liang, & Guo, ), but higher doses did not have any beneficial effects on antioxidant capacity, similar to previous results reported in cobia (Zhou et al, ), Chinese sucker (Huang et al, ) and gibel carp (Shao et al, ). The optimum vitamin C requirement for proper functioning of antioxidant capacity in Chu's croaker was estimated as 103.78 mg/kg based on liver SOD activity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the hepatic SOD, T‐AOC and CAT activities increased with vitamin C levels from 2.24 to 171.16 mg/kg, beyond which they decreased. These data suggested that, dietary vitamin C enhanced the hepatic SOD, T‐AOC and CAT activities (Cheng, Liang, & Guo, ), but higher doses did not have any beneficial effects on antioxidant capacity, similar to previous results reported in cobia (Zhou et al, ), Chinese sucker (Huang et al, ) and gibel carp (Shao et al, ). The optimum vitamin C requirement for proper functioning of antioxidant capacity in Chu's croaker was estimated as 103.78 mg/kg based on liver SOD activity.…”
Section: Discussionsupporting
confidence: 89%
“…The LZM activity is often used to evaluate the innate immune capacity of fish as it is ubiquitously distributed among living organisms (Saurabh & Sahoo, ). Furthermore, AKP is a polyfunctional hydrolase enzyme involved in the immune defence system of some fishes (Shao et al, ; Yan, Tian, Dong, Fang, & Yang, ). The AKP plays an important role in improving the recognition ability and phagocytosis by changing the surface structure of the pathogens and strengthening the disease resistance (Lazado, Lund, Pedersen, & Nguyen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Shao et al (2018) reported in gibel carp (Carassius auratus gibelio var.) fed with dietary L-ascorbic acid of 444.1 mg/kg in supplemented diet.…”
Section: Gonadosomatic Index In Koi Carpsupporting
confidence: 56%
“…Alkaline phosphatase is a multifunctional hydrolase enzyme having a role in the immunity of some fish species (Shao et al, 2018). It also has a role in identifying pathogen and phagocytosis by altering the surface structure of pathogens and improving disease resistance (Lazado et al, 2015).…”
Section: Ta B L Ementioning
confidence: 99%